Reproductive biology of the silver fish, Salmostoma phulo (Ham.), from Lower Manair reservoir, Karimnagar, Andhra Pradesh - Piska, Ravi Shankar; Waghray, Sarala; Prasad, M Ravindra (Indian Journal of Fisheries, 2011)
Varioui aspects of reproductive biology were studied on 812 Salmostoma phulo (Ham.) fuhet fromLower Manair reiervoir, Karimnagar, Andhra Pradeih, during 1987-88. Sex ratio wat 2.67:1 (F:M)and sexes were distributed homogeneously. Relative condition factor (Kn) and gonadosomaticindex (GSI) indicated spawing season and minimum size of maturity. The fecundity varied from 987to 2 729 ova in 54-87 mm long fishes. Minimum size at maturity was 43 mm for males and 44mm for females. The number of ova were distributed uniformaly in the entire ovary. The fish spawnedonly once in a year, with prolonged breeding season from April to October, peak period being fromJuly to September. It was a fractional spawner